Terminator 3 rise of the machines - Kassar, Mario; Vajna, Andrew G. (Burbank, CA : Warner Home Video, 2003)
John Connor is a 20-something living on the streets as a common laborer. His mother has since died, and their earlier efforts did not stop the creation of SkyNet artificial intelligence network. As he will still become the leader of the human resistance, Connor is once again targeted by a Terminator sent from the future by SkyNet. This new Terminator, T-X, is a female and is more powerful than any of her predecessors. To protect Connor, the human resistance sends a new T-101 back from the future
Producers, Mario F. Kassar, Andrew G. Vajna, Joel B. Michaels; director, Jonathan Mostow; screenplay, John Brancato, Michael Ferris; director of photography, Don Burgess; animator, C. Michael Easton; editor, Nicolas De Toth, Neil Travis; original music, Marco Beltrami; costume designer, April Ferry; production designer, Jeff Mann; visual effects supervisor, Don Lee; special effects, Robert DeVine
Performers: Arnold Schwarzenegger, Nick Stahl, Claire Danes, Kristanna Loken, David Andrews, Mark Famiglietti, Earl Boen, Moira Harris, Chopper Bernet
VCD Format
Keywords: Science fiction films; Cyborgs -- Drama; Artificial intelligence -- Drama